Local English teachers’ voices from a marginalized lens: Inequality practices and identity construction in the workplace - Sahril Nur; Ismail Anas; Reski Pilu; Nurfajriah Basri (JOALL (Journal of Applied Linguistics and Literature), 2022)
This article reports on a narrative case study that showcases the local English teachers’ perceived inequality practices and identity construction in Indonesia’s micro-reality context of a private language school domain. Grounded in the social theory of power, privilege, and positional identities, three synchronous online interviews were conducted to explore the LETs voices about what it means to experience the equality of rights and obligations in the workplace. As a result, the study revealed four inequality issues: (1) dissatisfaction with the payroll system, (2) the representation of gender and race in promotional endorsement, (3) the call for decolonizing pedagogy in ELT materials and resources, and (4) perceived identity as legitimate and qualified English teachers. Regarding the workload capacity and role as professional English teachers, they recognized that they deserve equal treatment as their native counterparts. However, this type of discrimination will further widen the gap between LETs and NESTs dichotomy and impede the construction of language teacher identity. This study suggests exploring dedicated strategies to develop information literacy skills for school principals, parents, teachers, students, and policymakers. This study will also contribute to the growth of critically oriented literature and scholarship on teacher identity and critical anti-racist language teaching pedagogy.